Warriors into Workers The Civil War and the Formation of the Urban-Industrial Society in a Northern City - Johnson, Russell L. (The North's Civil War, 2022)
In this portrait of Dubuque, Iowa, Russell Johnson combines personal narratives with social, political, and economic analysis to shed new light on what the War meant for one city and for the rapidly growing north. Johnson examines the experiences of Dubuque's soldiers and their families to answer crucial questions: What impact did the Civil War have on the economic and social life of Dubuque? How did military service affect the social mobility of veterans? And how did army service, as a form of industrial organization, help create a modern workforce? Warriors into Workers makes a significant contribution to our understanding of the formation of American industrial society, and addresses key issues in labor history, military history, political culture, and gender